The Effect Of Digital Transformation, Company Size, And Profitability Level On Tax Avoidance In Healthcare Companies On The Indonesia Stock Exchange In 2022-2024 - Purwanto, Ezsa Maharani (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: The goal of this research is to investigate how digital transformation, company size, and profitability influence tax avoidance behavior in healthcare companies listed on the Indonesia Stock Exchange (IDX) between 2022 and 2024. Background Problems: Despite post-pandemic performance growth (increased revenue, asset expansion, and digitalization) in the healthcare sector, the average Effective Tax Rate (ETR) remains lower than the applicable corporate tax rate, indicating an ongoing potential for tax avoidance. Novelty: This research introduces novelty by examining both the work environment and job satisfaction together as integrated factors affecting employee performance in the specific, under-researched context of the Singosari Industrial Training Center (BLKI Singosari). It aims to provide clarity by addressing the contradictory findings from previous studies on this topic. Research Methods: This study uses an associative quantitative approach with secondary data from annual financial reports. Data were analyzed using multiple linear regression, with the Effective Tax Rate (ETR) serving as the variable to measure tax avoidance. Finding/Results: Digital transformation, company size, and profitability together significantly impact tax avoidance.Digital transformation and company size have a significant individual impact on tax avoidance.Profitability has only a slightly significant individual effect. Digital transformation acts as a key driver that can reduce tax avoidance practices. Larger companies have greater scope for tax avoidance. Conclusion: It is concluded that digital transformation is an effective and significant factor that can reduce tax avoidance. Conversely, the results indicate that larger company size is associated with greater potential for tax avoidance practices.